(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
This article (peer reviewed) publishes, by adding the relevant footnotes, the paper read on October 21, 2014 during the Seminar on “Libertà religiosa e attività imprenditoriale for profit.Il caso Burwell v. Hobby Lobby, inc. (Supreme Court of the United States, June 30, 2014)” organized within the Scuola di Dottorato in Scienze Giuridiche (Curriculum in Storia del Diritto, Diritto Romano e Diritto delle Religioni, Diritto dell’Impresa) at Università degli Studi di Milano SUMMARY: 1. Foreword - 2. The issue(s) raised by Burwell v. Hobby Lobby, inc. - 3. Burwell v. Hobby Lobby, inc. main arguments - 4. Conclusions.